PEMANFAATAN LITERASI DIGITAL DALAM PENINGKATAN SKILL PEMROGRAMAN - Anita Sindar; Arjon Samuel Sitio; Feby Ginting; Sethu Ramen (LPPM Universitas HKBP Nommensen, 2023)
The dissemination of technological, scientific, social and cultural advances is very important to inform the community so that the implementation of learning activities is integrated with the educational curriculum. The development of science and technology must be applied directly and precisely to the school environment. Policy holders carry out strict supervision of school activities, especially so that students wisely, creatively and responsibly use digital devices. Achievement-based learning expands space for activities in formulating learning objectives. This activity applies the teaching model of lectures and practice (demonstrations). The fundamental role of the target audience is to increase the use of digital literacy media as a learning tool. The target of the activities for Grade 10 SMA Gajah Mada students aims to motivate students to explore their potential and talents by utilizing internet media as a learning resource according to the topics of interest. This activity utilizes digital hard and soft computer media.